HIV and leprosy coinfection: an integrative review about the challenges of diagnosis and treatment (Research, Society and Development, 2023)
To analyze the available scientific evidence published on HIV/leprosy coinfection about the diagnosis and treatment faced for the realization of adequate treatment for both pathologies. This is an integrative literature review in the SCOPUS, LILACS, Web of Science, Science Direct, PubMed, Embase and SCIELO databases. The final sample was composed of 12 publications, which addressed the diagnosis and treatment of HIV/leprosy coinfected persons. Most of the papers associated difficulties in diagnosing and treating individuals with both infections. The delay in diagnosis of HIV/leprosy coinfection is associated with difficulties in access to health services and diagnostic research, due to the deficit of scientific knowledge on the subject. More studies on this coinfection are necessary, considering the current scarcity. The articulation between the scientific community, specialized reference centers, and the inclusion of patients for an adequate diagnosis can mitigate the asphyxia resulting from infections and the necessary treatment.